Establishment and evaluation of a nomogram predicting risks of missed diagnoses of colorectal polyps - Xiaobo Wang; Haiyang Guo; Yong Tang; Lin Chen; Xianfei Wang (BMC Gastroenterology, 2022)
Abstract Background A missed diagnosis of colorectal polyps during colonoscopy may be associated with the occurrence of interval colorectal cancer. The risk factors for a missed diagnosis or a method to predict the risk of a missed diagnosis of colorectal polyps during colonoscopy remain unidentified. Methods The clinical data of patients who underwent two colonoscopies within three months at the Affiliated Hospital of North Sichuan Medical College between February 2017 and August 2019 were retrospectively reviewed. Independent risk factors for missed diagnoses were identified, and a nomogram was established to predict the risk of missed diagnoses. The prediction performance of the nomogram was evaluated using C-index and calibration curves, and its clinical application value was assessed using the Youden index and decision curve analysis. Results Independent influencing factors for missed diagnoses included age, endoscopist experience, bowel preparation, retroflected view, withdrawal time, number of polyps in the right colon, and number of polyps ≥ 6 mm. The C-index of the nomogram in the training and validation cohorts was 0.763 (95% confidence interval [CI]: 0.724 − 0.807) and 0.726 (95%CI: 0.657 − 0.794), respectively. The optimal cut-off value of the nomogram calculated using the Youden index was 152.2 points. Under the cut-off value, the sensitivity, specificity, positive predictive value, and negative predictive value were 67.1%, 75.7%, 45.8%, and 88.2%, respectively, in the training cohort, and 57.1%, 79.9%, 53.3%, and 82.3%, respectively, in the validation cohort. Conclusions The nomogram provides a reference value for clinicians to analyse the risk of a missed diagnosis of colorectal polyps in individuals, identify high-risk groups, and formulate appropriate follow-up strategies.